Therapies and Challenges in the Post-Stroke Aphasia Rehabilitation Arena: Current and Future Prospects - Georgiou, Anastasios M.; Kambanaros, Maria (My University, 2023)
Aphasia is a serious consequence of stroke that results in a breakdown in communication. The course of aphasia recovery differs between afflicted individuals, and responsiveness to treatment cannot be predicted. Aphasiologists continue to investigate numerous behavioral treatment protocols that have shifted their focus to complimentary rehabilitation strategies. The aim of this study is threefold. First, to summarize the different categories of aphasia interventions post-stroke, considering their respective protocols, and present available evidence on the effectiveness of those protocols. Second, to document the challenges regarding the prediction of aphasia treatment response post-stroke in individual patients. Third, to report the challenges faced by researchers in recruiting people with aphasia (PWA) for treatment studies, and provide recommendations on how to increase participant recruitment and retention. This study provides up-to-date information on (i) effective therapies and aphasia recovery processes, and (ii) research recruitment hurdles together with potential strategies for overcoming them.
Keywords: aphasia; recruitment; research